Cycling of Dense Core Vesicles Involved in Somatic Exocytosis of Serotonin by Leech Neurons - Trueta, Citlali; Kuffler, Damien P.; De-Miguel, Francisco F. (Frontiers in Physiology, 2012)
We studied the cycling of dense core vesicles producing somatic exocytosis of serotonin. Our experiments were made using electron microscopy and vesicle staining with fluorescent dye FM1-43 in Retzius neurons of the leech, which secrete serotonin from clusters of dense core vesicles in a frequency-dependent manner. Electron micrographs of neurons at rest or after 1 Hz stimulation showed two pools of dense core vesicles. A perinuclear pool near Golgi apparatuses, from which vesicles apparently form, and a peripheral pool with vesicle clusters at a distance from the plasma membrane. By contrast, after 20 Hz electrical stimulation 47% of the vesicle clusters were apposed to the plasma membrane, with some omega exocytosis structures. Dense core and small clear vesicles apparently originating from endocytosis were incorporated in multivesicular bodies. In another series of experiments, neurons were stimulated at 20 Hz while bathed in a solution containing peroxidase. Electron micrographs of these neurons contained gold particles coupled to anti-peroxidase antibodies in dense core vesicles and multivesicular bodies located near the plasma membrane. Cultured neurons depolarized with high potassium in the presence of FM1-43 displayed superficial fluorescent spots, each reflecting a vesicle cluster. A partial bleaching of the spots followed by another depolarization in the presence of FM1-43 produced restaining of some spots, other spots disappeared, some remained without restaining and new spots were formed. Several hours after electrical stimulation the FM1-43 spots accumulated at the center of the somata. This correlated with electron micrographs of multivesicular bodies releasing their contents near Golgi apparatuses. Our results suggest that dense core vesicle cycling related to somatic serotonin release involves two steps: the production of clear vesicles and multivesicular bodies after exocytosis, and the formation of new dense core vesicles in the perinuclear region.